2022
DOI: 10.1093/molbev/msac149
|View full text |Cite
|
Sign up to set email alerts
|

The Elephant Evolved p53 Isoforms that Escape MDM2-Mediated Repression and Cancer

Abstract: The p53 tumour suppressor is a transcription factor with roles in cell development, apoptosis, oncogenesis, ageing and homeostasis in response to stresses and infections. p53 is tightly regulated by the MDM2 E3 ubiquitin ligase. The p53-MDM2 pathway has co-evolved, with MDM2 remaining largely conserved while the TP53 gene morphed into various isoforms. Studies on pre-vertebrate ancestral homologues revealed the transition from an environmentally-induced mechanism activating p53 to a tightly regulated system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 107 publications
0
16
1
Order By: Relevance
“…This result contradicts previous results suggesting co-immunoprecipation of p53-R9 with MDM2 [1]. It remains possible that these two proteins interact, but that the interaction is weak as suggested recently by Padariya et al [34]. The mitochondrial pore protein cyclophilin D, which regulates necrotic cell death, co-immunoprecipitated with both elephant and human p53 [35].…”
Section: P53-r9 Binds Chaperone Tid1 To Localize At the Mitochondria ...contrasting
confidence: 88%
“…This result contradicts previous results suggesting co-immunoprecipation of p53-R9 with MDM2 [1]. It remains possible that these two proteins interact, but that the interaction is weak as suggested recently by Padariya et al [34]. The mitochondrial pore protein cyclophilin D, which regulates necrotic cell death, co-immunoprecipitated with both elephant and human p53 [35].…”
Section: P53-r9 Binds Chaperone Tid1 To Localize At the Mitochondria ...contrasting
confidence: 88%
“…A p53-mediated apoptotic response to SIPs was also observed in a previous study with elephant fibroblasts. It was shown that the expansion of TP53 copy number in elephants (20 copies) with several TP53 retrogenes showing expression could be responsible for this phenotype [14, 15, 50]. We analyzed genomes of several bat species to see if TP53 copy number expansion has occurred in Chiroptera (Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the p38 paralogs’ fate, we inferred a phylogenetic tree with an extended dataset for vertebrates. We included species relevant for our study such as whales and elephants due to a link between large body size and cancer resistance [2931] and bats or naked mole rat as animals with a special immune system [32,33]. Altogether, we collected 294 protein sequences from 63 species (electronic supplementary material, table S3).…”
Section: Resultsmentioning
confidence: 99%